2017
DOI: 10.1002/hep.29273
|View full text |Cite
|
Sign up to set email alerts
|

The PNPLA3 variant associated with fatty liver disease (I148M) accumulates on lipid droplets by evading ubiquitylation

Abstract: A sequence variation (I148M) in patatin-like phospholipase domain-containing protein 3 (PNPLA3) is strongly associated with fatty liver disease (FLD), but the underlying mechanism remains obscure. Here we used knock-in (KI) mice (Pnpla3148M/M) to examine the mechanism responsible for accumulation of triglyceride (TG) and PNPLA3 in hepatic lipid droplets (LDs). No differences were found between Pnpla3148M/M and Pnpla3+/+ mice in hepatic TG synthesis, utilization, or secretion. These results are consistent with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
207
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 219 publications
(218 citation statements)
references
References 40 publications
(102 reference statements)
6
207
0
2
Order By: Relevance
“…PNPLA3 has been attributed a retinyl‐palmitate lipase activity in hepatic stellate cells (HSC), and stable overexpression of PNPLA3 rs738409[G] was associated with decreased retinol release from human HSC ex vivo and concomitantly impaired reduction in fibrogenic factors . Recently, the rs738409[G] variant has been shown to disrupt ubiquitination and proteasomal degradation of PNPLA3, resulting in accumulation of PNPLA3‐148M and impaired mobilization . Interestingly, hepatic levels of retinol dehydrogenase 16 (RDH16), a critical microsomal regulator in the generation of all‐trans‐retinoic acid, were significantly lower in homozygous PNPLA3 rs738409[G] carriers than in patients with homozygous wild‐type allele and directly associated with stage of fibrosis.…”
Section: Discussionsupporting
confidence: 91%
“…PNPLA3 has been attributed a retinyl‐palmitate lipase activity in hepatic stellate cells (HSC), and stable overexpression of PNPLA3 rs738409[G] was associated with decreased retinol release from human HSC ex vivo and concomitantly impaired reduction in fibrogenic factors . Recently, the rs738409[G] variant has been shown to disrupt ubiquitination and proteasomal degradation of PNPLA3, resulting in accumulation of PNPLA3‐148M and impaired mobilization . Interestingly, hepatic levels of retinol dehydrogenase 16 (RDH16), a critical microsomal regulator in the generation of all‐trans‐retinoic acid, were significantly lower in homozygous PNPLA3 rs738409[G] carriers than in patients with homozygous wild‐type allele and directly associated with stage of fibrosis.…”
Section: Discussionsupporting
confidence: 91%
“…Inhibition of autophagy promotes accumulation of the wild‐type protein, but not the I148M variant, suggesting that this mutation renders the protein resistant to autophagic degradation. These data are consistent with previous work, showing that PNPLA3 I148M is resistant to ubiquitylation . Building on this, expression of a ubiquitylation‐resistant form of wild‐type PNPLA3 increased protein abundance and promoted TAG accumulation to similar levels observed with the I148M variant.…”
Section: Mechanism Debatedsupporting
confidence: 92%
“…The mechanism by which PNPLA3(148M) promotes hepatic steatosis has remained elusive despite extensive studies in vitro , in cultured cells, and in animal models . It has been suggested that PNPLA3(148M) promotes steatosis by increasing TG synthesis or by impairing TG secretion from hepatocytes, but we have not been able to confirm either of these possibilities .…”
Section: Discussionmentioning
confidence: 95%
“…Once on the LD, PNPLA3(WT) is rapidly degraded. The rapid turnover of the protein limits accumulation of PNPLA3(WT) on LDs (left) . In contrast to the WT protein, PNPLA3(148M) is poorly ubiquitylated and accumulates on LDs (right) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation